Overmacht As The Basis of Giving Stimulus To Bank Customers Affected By Covid 19 - Hascaria Budi Prasetyo (Faculty of Law, Merdeka University Surabaya, 2020)
The Covid 19 pandemic has seriously hurt the global economy both at micro and macro levels. The impact of the Covid 19 pandemic in the form of workers losing their jobs and several business sectors unable to operate again, this causes debtors to be unable to pay off creditors' debts and causes defaults in accordance with agreements agreed upon by banks and debtors. The impact of covid 19 can be categorized as a state of force / overmacht, so that the Government through the Financial Services Authority makes a rule that banks can provide stimulus facilities for bank debtors as. This study aims to determine the limit of the stimulus provided by banks to debtors who are affected by covid 19.